Ashes of a memory [videorecording] - Celdran,David; Boncan, Jam N. (Skycable New Production, 1997)
A documentary on the fire disaster of Ozone Disco in Quezon City that took 162 lives on March 19, 1996. Features the names and pictures of those who were burned and died in the fire.